The Impact of Celebrity Endorsement on Brand Awareness of Childrenswear - Tsabitha, Nabila; Rachmawati Chaldun, Evy (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. The market of childrenswear in Indonesia is emerging and promising. However, as the competitiveness is relatively high, the right marketing strategy is needed to compete in the market. Brand awareness is one of determining factors in the purchasement of a product. That is why a business should really pay attention on its brand awareness. Celebrity endorsement is a marketing strategy which one of its benefits is to increase brand awareness. This research has aim to investigate the impacts of the factors in celebrity endorsement when used by childrenswear brands to increase their awareness. The data of this research gathered from online questionnaires spread to 210 respondents of Indonesian mothers considered as the target market of childrenswear. The relationship between the independent variables of endorser’s credibility, endorser’s attractiveness, and match up/product fit towards dependent variable of brand awareness is analyzed using multiple linear regression. Based on the respondents’ assessment, celebrity endorsement done by childrenswear brands perceived positively by the respondent. The result of statistical analysis indicates that there is correllation between celebrity endorsement and brand awareness in 22% variances. However, from the three factors analyzed, only the factor of endorser’s attractiveness has significant impact in raising brand awareness of childrenswear. Keywords: Brand Awareness, Celebrity Endorsement, Childrenswear, Indonesian Market